Dysbiosis Anticipating Necrotizing Enterocolitis in Very Premature Infants. (23rd October 2014) - Sim, Kathleen; Shaw, Alexander G.; Randell, Paul; Cox, Michael J.; McClure, Zoë E.; Li, Ming-Shi; Haddad, Munther; Langford, Paul R.; Cookson, William O. C. M.; Moffatt, Miriam F.; Kroll, J. Simon
Abstract : Using 16S rRNA gene sequencing and targeted culture, we compared microbiota in fecal samples from infants with necrotizing enterocolitis (NEC) and controls. Two significant signatures were associated with NEC: 1 with dominant Clostridium perfringens and 1 with dominant Enterobacteriaceae. Abstract: Background. Necrotizing enterocolitis (NEC) is a devastating inflammatory bowel disease of premature infants speculatively associated with infection. Suspected NEC can be indistinguishable from sepsis, and in established cases an infant may die within hours of diagnosis. Present treatment is supportive. A means of presymptomatic diagnosis is urgently needed. We aimed to identify microbial signatures in the gastrointestinal microbiota preceding NEC diagnosis in premature infants. Methods. Fecal samples and clinical data were collected from a 2-year cohort of 369 premature neonates. Next-generation sequencing of 16S ribosomal RNA gene regions was used to characterize the microbiota of prediagnosis fecal samples from 12 neonates with NEC, 8 with suspected NEC, and 44 controls. Logistic regression was used to determine clinical characteristics and operational taxonomic units (OTUs) discriminating cases from controls. Samples were cultured and isolates identified using matrix-assisted laser desorption/ionization–time of flight. Clostridial isolates were typed and toxin genes detected. Results. A clostridial OTU was overabundant in prediagnosis samples from infants with established NEC ( P = .006). Culture confirmed the presence of Clostridium perfringens type A. Fluorescent amplified fragment-length polymorphism typing established that no isolates were identical. Prediagnosis samples from NEC infants not carrying profuse C. perfringens revealed an overabundance of a Klebsiella OTU ( P = .049). Prolonged continuous positive airway pressure (CPAP) therapy with supplemental oxygen was also associated with increased NEC risk. Conclusions. Two fecal microbiota signatures ( Clostridium and Klebsiella OTUs) and need for prolonged CPAP oxygen signal increased risk of NEC in presymptomatic infants. These biomarkers will assist development of a screening tool to allow very early diagnosis of NEC. Clinical Trials Registration. NCT01102738.